Orquestração de recursos em ecossistemas digitais: um estudo de caso no agronegócio digital - Boelter, Diego (Universidade do Vale do Rio dos Sinos, 2025)
This study investigates resource orchestration in digital ecosystems, focusing on agribusiness, and explores how companies organize, combine, and leverage resources to generate competitive advantage. The research adopts a single case study of Orbia, a well-established digital platform in the agricultural sector, analyzing its resource orchestration mechanisms and value creation strategies. The theoretical framework is based on the Resource-Based View (VBR) and its evolution into Resource Orchestration, which emphasizes the strategic mobilization of internal and external assets to drive innovation and sustainability in digital ecosystems. The methodology is qualitative, employing document analysis and semi-structured interviews to capture the orchestration dynamics within Orbia. Data analysis is coded using the template analysis methodology. The results indicate that competitive advantage in digital ecosystems does not stem solely from possessing valuable resources but from the ability to efficiently manage and combine them in collaboration with strategic partners. The study highlights the central role of resource orchestration and cooperation among ecosystem actors, demonstrating that successful digital platforms operate through strategic interdependence among complementary companies. The contributions of this research are both theoretical and practical. Theoretically, the study reinforces the relevance of Resource Orchestration as an extension of VBR in digital environments. From a managerial perspective, it provides insights into how companies can structure their digital ecosystems to maximize value and competitiveness. The study presents some limitations, such as analyzing a single case, which may restrict the generalization of findings. As a suggestion for future research, it is recommended to explore multiple digital ecosystems across different sectors to broaden the understanding of resource orchestration strategies.
Keywords: Orquestração de recursos; Ecossistemas digitais; Competitividade; Visão Baseada em Recursos (VBR); Agronegócio; Vantagem competitiva; Análise de template; Resource orchestration; Digital ecosystems; Competitiveness; Resource-Based View (VBR); Agribusiness; Competitive advantage; Template analysis; ACCNPQ::Ciências Sociais Aplicadas::Administração